DEVELOPMENT OF SCIENTIFIC APPROACHES TO THE RESEARCH OF THE MANAGEMENT NATURE OF ENTERPRISE CAPITAL - Frolova Larysa Volodumurivna; Melnyk Oksana Volodimirivna; Shevchuk Nataliia Valentinivna; Magdaliuk Oleksii Vitaliyovych (Scientific Journal of Pedagogy and Economics, 2019)
The scientific article is devoted to the problems of research of the managerial nature of the capital of the enterprise, which has undergone significant changes in recent years. On the basis of a critical analysis of scientific work on substantive interpretations of the enterprise capital, approaches to their research are organized, organized into the following: economic, according to which capital is explored as wealth, money, resources, value, etc.; accounting, within which the interpretation of capital is carried out in terms of financial results, net assets, financial resources, etc.; financial, according to which capital is considered as a form of organization of financial resources, stock of funds, monetary measurement values. Postindustrial specificity of social development directly reflected on the processes and results of capital management of the enterprise, which actualized the study of capital in the entrepreneurial aspect. It is determined that the difference between this approach and traditional research is the focus on such forms of capital as social, information, knowledge, technological, cultural, etc., which is caused by the postindustrial specificity of processes of human being. However, under such conditions, forms of capital are not able to perform their functions without being involved in the interaction and relationships mediated by the activities of economic entities on the basis of mutual value. The entrepreneurial problematics of enterprise capital research has led to changes in the logic of managerial influences on it, which should be implemented in accordance with a strategic-oriented approach. Its main specificity is related to the expansion of the content space of capital research - not only objective but also incorporated, as well as the implementation of management based on the elimination of extraordinary and ordinary gaps in the results of capital formation processes